Measuring The Impact Of The Effectiveness Of A Training Program According To The Dimensions Of Professional Motivation In Improving Job Satisfaction For Accountants - Kadhim Al-Abboodi, Mohammed; Fakhfakh, Mondher (International Journal of Economics, Management and Accounting, 2025)
The research aims to measure the effectiveness of a training program according to the dimensions of professional motivation for accountants and its impact on improving job satisfaction by verifying the validity of the following null hypothesis: "There is no statistically significant difference at a significance level of (0.05) between the average scores of the experimental group who will undergo training in the program prepared according to the dimensions of professional motivation, and the average scores of the control group who will not undergo training in the training program in job satisfaction." To achieve the objectives of the research, the researchers used the experimental design with two equivalent groups (experimental and control), as (42) accountants were selected randomly (by lottery) as a sample for the research from the accountants affiliated with the General Directorate of Education in Qadisiyah for the academic year (2024 - 2025), with (21) accountants for the experimental group and (21) accountants for the control group. The training program was built according to three stages (planning, design, evaluation), and then the accountants of the experimental group were trained for (11) days with two sessions per day using the training program according to the dimensions of professional motivation. The researcher also prepared a scale for technical enlightenment of the multiple-choice type (40 paragraphs), and their validity and stability were verified, as the stability coefficient for the scale test reached (0.91) and the stability coefficient for the observation card reached (0.87), for the scale test (0.89) and they were applied after the end of the experiment. The researcher used the statistical program SPSS. The accountants of the experimental group outperformed the accountants of the control group in the job satisfaction scale test, and in light of the research results, the researcher recommended the possibility of adopting the training program prepared according to the dimensions of professional motivation.